THE EFFECT OF SOCIAL MEDIA ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER RELATIONSHIP MANAGEMENT - Suryanto, Nadira Maysa; Sri Palupi Prabandari (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
Several marketing approaches in the digital marketing era are marketing products and gaining consumer reach through several relationships between marketers and con-sumers before, during, and after product purchases. To overcome business competition in the garment sector, the company's efforts to maintain the company's existence are to focus on building relationships with cus-tomers. The research aims to investigate the effect of Social Media on Customer Loyalty Mediated by Customer Relationship Management on Vido Garment. This study employed quantita-tive and explanatory methods to determine the relationship between the variables through hypothesis testing. The study was conducted using a purposive sampling method with a total sample of 160 Vido Garment customers who had placed orders through question-naires distributed online and offline. The data collected had been processed using Partial Least Square (PLS) with the help of SmartPLS 3 software. The hypothesis testing used a bootstrapping system to get the T-Statistic and P-Value values. This study indicates that Social Media has a positive and significant effect on Customer Loyalty Mediated by Customer Relationship Management.